Bio-B / Nur Fatihah Zulkfli … [et al.] - Zulkfli, Nur Fatihah; Azni, Nur Athirah Afiqah; Nor Azman, Nur Fatihah; Othman, Nur Khaleeda; Wan Buanan, Wan Nur Fatihah; Mohd Nordin, Noorain (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Malaysia nowadays faces solid waste and difficulty in composting food waste as it is more expensive in Malaysia than in other nations due to high manufacturing costs. The point is two of three are the primary environmental concerns of Malaysia. It has a profound impact on Nature's ability to sustain living within its capacity. Malaysia now produces approximately 23,000 tons of trash on a regular basis. Nevertheless, in 2020, this amount is predicted to surge to 30,000 tons. According to the SWCorp, Malaysians have generated sufficient food wasted per day to fill seven Olympic-sized swimming pools. Furthermore, according to McFall Johnsen (2022), following the release of the United Nations' shocking new climate report recently, over 1000 scientists protested throughout the globe including a NASA climatologist. Scientists fastened themselves to the doors of oil-friendly bank banks, stopped highways, and occupied government buildings. They protested on stopping the production of fossil fuels that derived from the decomposition of plants and animals. These fuels, which may be found in the Earth's crust and include carbon and hydrogen, can be burnt for energy. Fossil fuels include coal, oil, and natural gas. The fossil fuels have caused the biggest climate changes and the scientist predicts earth can only last for 3 years Thus, DE ‘Einstein has come out with a new innovative product that can save the earth from the rise of environmental concerns named BioB. We mainly provide a product that has an auto sensor, which can compost food waste and sort the trash by its’ categories. Our objective focuses on sustainability and making use of our biodegradable dustbin that can give benefits and not to forget creating the awareness of 3R (Reuse, Reduce, Recycle) towards societies.